Effects of plyometric training on jumping, sprint performance and lower body muscle strength in healthy adults: A systematic review and meta-analyses - Oxfeldt, M.; Overgaard, K.; Hvid. L. G.; Dalgas, U. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Objective: To determine the effect of lower-body plyometric training (PLY) on jumping, sprint performance and lower body muscle strength in healthy adults. Methods: A systematic literature search (Pubmed, Embase) was performed. Studies were included if they 1) described a lower-body PLY intervention lasting = 4weeks; 2) included measures of jumping, sprint and/or lower body muscle strength; 3) included healthy individuals = 18 years; 4) included a training or non-training control group; 5) were written in English. Meta-analyses identifying the effects of PLY on jumping, sprint and lower body muscle strength were conducted providing the standardized mean difference (SMD). Results: 826 records were identified of which 25 fulfilled the inclusion criteria, yielding 19, 11 and 7 data points for the meta-analyses of jumping, sprint performance and lower body muscle strength respectively. The data showed improvements for all three performance variables after 4-12 weeks of PLY. The SMD [CI95%] across studies for jump height, sprint time and muscle strength were 0.45 [0.16: 0.75], - 0.59 [- 1.01: - 0.17] and 0.33 [0.03: 0.63], respectively, where the latter two showed within-sample heterogeneity. Conclusion: The systematic review and meta-analyses showed that PLY elicits a small to moderate positive effect on jumping, sprint performance and lower body muscle strength in healthy adults being recreationally active or athletes.